Reconstruction of Indigenous Knowledge into Scientific Knowledge in the Production Process of Batik Linggo - Riky Setiawan; Wibowo, Teguh; Ariyatun (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
This study aims to reconstruct indigenous knowledge into scientific knowledge in the production process of Batik Linggo carried out in Singorojo District, Kendal Regency, Central Java, Indonesia. The description of this study is a number of scientific knowledge from the reconstruction of indigenous knowledge about the production of Batik Linggo. This study uses a qualitative descriptive method through interviews, direct observation, and literature study on the production of Batik Linggo. This research focuses on the Production Process description of Batik Linggo, especially the knowledge of Batik craftsmen related to raw materials and the production process of Batik Linggo. The data obtained were analyzed, verified, constructed into scientific knowledge, and interpreted to obtain meaningful information. Based on this research, it can be concluded that there is local wisdom found in the production of Batik Linggo that can be reconstructed into scientific knowledge.